Recurrent endometrial atypical hyperplasia diagnosed by pathological examination of the placenta from a live birth: a case report - Weilu Wu; Wei Wang; Juan Zou (BMC, 2023)
Abstract Background Pregnancy complicated with endometrial atypical hyperplasia, which is often observed during early pregnancy, is extremely rare. Case presentation The patient was a 30-year-old woman who had premature delivery at 30+ 1 weeks gestation, and endometrial atypical hyperplasia was discovered by placental examination. Conclusions For patients who undergo fertility-sparing treatment for endometrial atypical hyperplasia, the evaluation of the decidua via the placental pathological examination is particularly important. These examinations make a great clinical contribution to the early detection and diagnosis of endometrial atypical hyperplasia.